Onjisaponin B (OB) is Neuroprotective During Cognitive Loss Through Immune-mediated and SIRT1 Pathways - Li, Xinyu; Sun, Yu; Wei, Yafen; Zhou, Lihong; Liu, Li; Yin, Ping; Liu, Yongdan; Wu, Shanshan; Li, Jingxin; Lu, Chong (Current Neurovascular Research, 2018)
Background: The purpose of the present study was to investigate the effects of Onjisaponin B (OB) in lipopolysaccharide (LPS)-induced cognitive deficits. Methods: The rats were divided into four groups: sham group, LPS group (the model group), LPS + OB (1 mg/kg) group and LPS + OB (2 mg/kg) group. OB was treated three days before surgery and thereafter continuously for 7 days. Three days later, rats were intracerebroventricularly injected with LPS. The levels of inflammatory cytokines and the capability of free radical scavenging in serum and hippocampus were determined after the LPS challenge. PC12 cells were divided into control group, LPS group (the model group), LPS + OB (10 μM) group, LPS + OB (20 μM) group, LPS + OB (40 μM) group, LPS + OB (2 mg/kg) + nicotinamide group. The cell viability was measured by MTT assay. The protein expressions of Sirt1, p-AMPK, AMPK, Nrf-2, HO-1, Bcl-2, Bax, caspase-9, caspase-3, p-IΚBα, IΚBα, p-NF-ΚBp65 and NF-ΚBp65 were detected by western blot analysis. Results: As a result, OB administration effectively relived the cognitive impairment, reduced the contents of IL-1β, IL-6, TNF-α, MDA and restored SOD activities of SOD in serum and hippocampus of LPS-induced rats. Furthermore, OB treatment improved cell viability, ameliorated the alterations of IL-1β, IL-6, TNF-α, MDA and SOD in the supernatant of LPS-induced PC12 cells. Of note, the expressions of Sirt1, Nrf-2, HO-1, Bcl-2 and p-AMPK were downregulated, while Bax, caspase-9, caspase-3 and the phosphorylations of IΚBα and NF-ΚBp65 in the LPS-stimulated hippocampus and PC12 cells were increased attributed to the LPS stimulation. Nevertheless, the conditions were significantly attenuated by OB treatment. In the LPS-induced PC12 cell, nicotinamide, a SIRT1 inhibitor, abrogated the beneficial effects of OB, as indicated by the antioxidant, anti-inflammatory and anti-apoptosis signaling. Conclusion: Based on the above evidence, our results demonstrated that OB was a potential therapeutic candidate for LPS-induced cognitive deficits.
Keywords: anxiety disorders